Vaginal microbiota: different roles of lactobacilli and community instability in chronic vulvovaginal discomfort - Buchta, Vladimír; Nekvindová, Jana; Leško, Daniel; Vrbacký, Filip; Veščičík, Peter; Uhlířová, Zuzana; Andrýs, Ctirad; Bolehovská, Radka; Kacerovský, Marian; Špaček, Jiří; Mrkvicová, Alena; Skalská, Hana; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundChronic vulvovaginal discomfort (CVD) is a complex syndrome with many unresolved questions regarding its etiology, diagnosis, and management in relation to the vaginal microbiota.MethodsCervicovaginal fluid of 91 CVD patients and 35 healthy controls was obtained at the beginning and end of the follow-up period. The bacterial community state types (CST) in the vagina were assessed using next-generation sequencing (NGS). CVD patients were divided into four study groups by etiology: non-specific, yeast, bacterial, and mixed.ResultsThe vaginal microbiota was characterized by 1) predominance of CST3 in all study groups, 2) a relatively higher proportion of CST2 (29.2%) and CST4 (20.0%) in the non-specific group and controls, respectively, 3) lack of CST4 (4.0%) in the yeast group, and 4) an effect of clinical status (CVD vs. health) on CST stability and microbiota composition. The vaginal environment was shaped by lactobacilli except for CST4. CVD patients had a higher proportion of G-positive cocci than controls; the non-specific group had significantly higher L. gasseri abundance than other CVD etiologies. There was a negative correlation between L. crispatus and L. iners, between G-positive cocci and L. iners, and a positive correlation between G-positive cocci and non-bivia Prevotella species. CST3 in CVD patients represented the most stable CST and was the community to which other CSTs were most often converted, whereas in healthy controls, CST3 was the most labile CST, with a preferential shift to CST4. The distribution of unstable CSTs was similar in both main cohorts, but within CVD group, non-specific etiology showed significantly higher proportion of unstable CSTs and L. gasseri.ConclusionOur results revealed an opposing trend in the abundance of L. iners and L. gasseri between CVD patients and healthy controls, depending on CST stability. We hypothesize that the increased prevalence of CST2 and CST3 may result either from persistent CVD-associated pressure (CST2 and partially CST3), or from enhanced community stability (CST3). The finding that the importance and behavior of Lactobacillus species depend on the patient’s clinical status and microbiota context (CST) should contribute to more accurate diagnoses (correct interpretation of laboratory findings) and management of CVD.